La vulneración de derechos por la publicidad de información en el sistema e-SATJE - Sánchez Alejandro, Melissa Paola (2023)
This paper analysed the violation of rights resulting from the disclosure of information contained in the automatic system of Ecuadorian judicial procedure eSATJE, within the framework of the constitutional state of rights and justice. The methodology was descriptive, non-experimental and cross-sectional, it started from a mixed approach (qualitativequantitative), and it used the inductive-deductive, historical-logical, analytical-synthetic, comparative and dogmatic methods, as well as bibliographic review techniques, indexing, documentary review of sentences, and a survey. As a result, it was theoretical justified that the disclosure of information contained in the Ecuadorian automatic judicial processing system eSATJE, causes violation of constitutional rights such as: discrimination due to the judicial past, the right to honour and good name, privacy and the protection of personal data; therefore, it is considered essential to restrict access to this system, in order for the use and operation to be directed towards the procedural parties and their duly authorized technical defenders.